The First World War and Town Children (Theatrum historiae, 2015)
The paper deals with the negative effects which town children were exposed to in the war years 1914–1918. On the basis of the explored sources, primarily sources of a personal nature, school records, period scientific literature and periodicals, it is possible to say that what the long 19th century tried to improve in the status of a child (granted education, medical care, family relationships, and the adequacy of dressing and boarding), the war denied again.
Keywords: history of childhood; the First World War; pathology of childhood; rationing; history of education